1971
DOI: 10.1021/jo00803a004
|View full text |Cite
|
Sign up to set email alerts
|

Base-promoted reactions of epoxides. VI. Bicyclo[2.2.1]heptene and bicyclo[2.2.2]octene oxides

Abstract: The details of the previously observed lithium diethylamide isomerization of 2,3-epoxybicyclo [2.2.1] heptane to nortricyclanol have been examined. By deuterium labeling methods, it has been shown that reversible metalation occurs a t the epoxide ring and that base attack does not remove the ex0 hydrogens of the transannular bridge.The endo-5-methyl derivative 5 is transformed into the analogous tricyclic alcohol 7, whereas epoxide 6, with both transannular endo positions blocked with methyl groups, isomerizes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1973
1973
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Heating of norbornene oxide ( 79 ) with lithium diethylamide in benzene gave nortricyclanol ( 80 , Scheme ) . The carbenoid mechanism of this reaction was confirmed by using deuterium-labeled epoxide 81 . When epoxide 81 was treated under the same conditions, nortricyclanol 83 was obtained and it was found that all the deuterium label was retained.…”
Section: Base-promoted Isomerization Of Epoxides With C−h Insertionmentioning
confidence: 90%
“…Heating of norbornene oxide ( 79 ) with lithium diethylamide in benzene gave nortricyclanol ( 80 , Scheme ) . The carbenoid mechanism of this reaction was confirmed by using deuterium-labeled epoxide 81 . When epoxide 81 was treated under the same conditions, nortricyclanol 83 was obtained and it was found that all the deuterium label was retained.…”
Section: Base-promoted Isomerization Of Epoxides With C−h Insertionmentioning
confidence: 90%
“…The predominance of this pathway over other possible pathways has been attributed to conformational properties of the lithiooxirane intermediate 5,26 ; for the same reason, this predominance can be precluded for substituted medium-size oxiranes 244 . This reaction is also widely observed in the case of bicyclic oxiranes where Bredt's rule and the blocked conformation (see Section II.A) precludes the allylic alcohol formation, such as norbornene oxide 17 254,255 . However, it has been very seldom reported in the case of linear oxiranes 256 .…”
Section: Electrophilic Reactions Of Lithiooxiranesmentioning
confidence: 65%
“…This epoxide is known to give the 1,3-carbenoid C-H insertion product (alcohol 40) upon treatment with organolithium reagents (Scheme 9). [36,[40][41][42] Scheme 9.…”
Section: Wwweurjocorgmentioning
confidence: 99%